Resultados do Retalho Vertical do músculo Reto Abdominal modificado na cicatrização perineal após amputação abdominoperineal extraelevadora para Adenocarcinoma de Reto - Renato Gomes Campanati (2023)
The extralevator abdominoperineal excision of the rectum (ELAPE) consists of the transection of the levator ani muscles at its lateral attachments on the pelvis, in order to reduce intraoperative rectal perforation and positive circumferential resection margin. However, the pelvic defect after ELAPE is wider than after conventional abdominoperineal resection and with a greater risk of perineal wound complications. Several different reconstruction techniques have been proposed from primary suture of the skin, to flap and mesh closure. This thesis aims to describe the technique of the modified vertical abdominis muscle flap reconstruction and to compare the perineal wound healing outcomes with that of other closure methods. This is a retrospective cohort from August 2013 to August 2022 of patients submitted to extralevator abdominoperineal excision of the rectum. Patients were categorized according to the pelvic reconstruction method. Primary outcome was perineal wound complications until 30 days of surgery. Secondary outcomes were total postoperative complications, mortality, perineal wound complications after 30 days, operative time, intraoperative transfusion rate and length of stay. Categorical variables were analyzed with the Chi-Square and the Fisher methods, while nonparametric continuous variables were compared using the Mann-Whitney test. In the given period 74 patients were submitted to extralevator abdominoperineal excision of the rectum, with 35,1% (n=26) being reconstructed with the mVRAM flap. Half of the patients (n=37) were male and 85,1% (n=63) were submitted to preoperative chemoradiation. The perineal wound complication rate until 30 days was 38,6% (n=27), being mostly surgical site infection (22.9%; n=16) and wound dehiscence (11.4%; n=8). The mVRAM presented lower incidence of perineal wound complication until 30 days in comparison to all other methods combined (12% vs 53.3%; p=0.001), to primary suture (12% vs 56.5%; p=0.001), to gluteus maximus flap (12% vs 46,7%; p=0.014) and to biological prosthesis of bovine pericardium (12% vs 57.1%; p=0.011). In addition, none of the complications of the mVRAM group were classified as major, Clavin-Dindo classification grades III and IV, compared to 35.6% (p=0,008) of all other methods combined. The median operative time of the mVRAM flap group was statistically different only in the analysis with the primary suture group (300 minutes vs 250 minutes; p=0.021). There was no donor site morbidity related to the mVRAM flap. In summary, pelvic reconstruction with the mVRAM flap after ELAPE showed a lower perineal wound complication rate until 30 days and lower major postoperative complication rate, with no difference on the operative time and length of stay.